# Series and sequences

Printable View

• Oct 4th 2012, 02:41 AM
AuXian
Series and sequences
Can somebody teach me how to solve this question? Please…

Sorry... since i don't know how to write the symbols here... so i used attachment...
• Oct 4th 2012, 03:06 AM
emakarov
Re: Series and sequences
Quote:

Originally Posted by AuXian
Show that $\displaystyle \sum_{n=1}^r\frac{r^2+r^{-1}}{r^2+r}=\frac{n^2}{n+1}$

So, are you summing r constants (i.e., expressions that don't depend on n)?
• Oct 4th 2012, 03:25 AM
johnsomeone
Re: Series and sequences
If it's $\displaystyle \sum_{r = 1}^n \frac{r^2 + r^{-1}}{r^2 + r} = \frac{n^2}{n+1}$, then it isn't even true.

$\displaystyle n =1:$ LHS $\displaystyle = \frac{1^2 +1^{-1}}{1^2 + 1} = \frac{2}{2} = 1$. RHS $\displaystyle = \frac{1^2}{1+1} = \frac{1}{2}$.

$\displaystyle n =2$: LHS $\displaystyle = (1) + \frac{2^2 +2^{-1}}{2^2 + 2} = 1 + \frac{4.5}{6} = \frac{7}{4}$. RHS $\displaystyle = \frac{2^2}{2+1} = \frac{4}{3}$.
• Oct 4th 2012, 06:13 AM
AuXian
Re: Series and sequences
Quote:

Originally Posted by emakarov
So, are you summing r constants (i.e., expressions that don't depend on n)?

ya... only the final step will convert r to n... It is needed to show that LHS=RHS, the LHS will be used. My problem is, I don't know how to simplify the earlier part (about r)...(Crying)
• Oct 4th 2012, 07:42 AM
emakarov
Re: Series and sequences
Quote:

Originally Posted by AuXian
only the final step will convert r to n...

I am not sure what this means. Please write the question correctly.
• Oct 4th 2012, 08:09 AM
AuXian
Re: Series and sequences
Quote:

Originally Posted by emakarov
I am not sure what this means. Please write the question correctly.

What i wrote there is a complete question....
• Oct 4th 2012, 08:15 AM
emakarov
Re: Series and sequences
Quote:

Originally Posted by AuXian
What i wrote there is a complete question....

And yet you had to add the phrase "only the final step will convert r to n," the meaning of which I don't understand. Even worse, the left-hand side of the equation in the quote in post #2 does not depend on n (n is a bound variable used as the summation index) while the right hand side does. And if n and r are reversed, then, as post #3 shows, the equation is incorrect.